The Relationship Between Intrinsic Religiosity and Resilience Among Tunisian Female University Students - Salma Derouiche-El Kamel; Yassamine Hentati (European Scientific Journal, ESJ, 2025)
This study aimed to explore the relatively under-examined relationship between intrinsic religiosity and resilience among Tunisian female university students. A sample of 244 students participated by completing two scales: the "Arabic Scale of Intrinsic Religiosity" (Abdel-Khalek, 2017) and "The Tunisian Resilience Scale" (Derouiche-El Kamel & Hentati, 2021). Data analysis involved correlation and linear regression methods. A significant positive correlation (p<0.000) emerged between the two variables among the students. Moreover, intrinsic religiosity was found to predict resilience scores (p<0.000). These findings suggest a meaningful association between intrinsic religiosity and resilience among Tunisian female students. The study implies that intrinsic religiosity could serve as a predictive factor for resilience, shedding light on its potential role in fostering resilience among this population.